Clinical and morphological features of diffuse gliomas in population of Kharkiv region from 2000 to 2014 - Chertenko, T. N.; Yakovtsova, I. I. (Морфологія / Morphologia / Morfologìâ, 2016)
Background. Diffuse glioma is one of the most common among tumors of the central nervous system (CNS). Epidemiological and morphological researches of diffuse gliomas allow to find the most prevalent histotypes of these tumors in Kharkiv region. Objective. To study the outer appearance and histological structure of diffuse gliomas in population of Kharkiv region. Methods. The research is based on case histories of patients with tumors of central nervous system and their biopsies in the period from 2000 to 2014. The statistical data was processed with Microsoft Excel. Results. We analysed data from 1540 case histories of patients with primery incidence of CNS tumors in Kharkiv and Kharkiv region from 2000 to 2014. Overall, approximately 42,4% of all tumors are diffuse gliomas (653 cases). Among diffuse gliomas the most common is glioblastoma. It accounts 54,8% of diffuse gliomas and 25% of all primary CNS tumors. This data is higher than the rate of glioblastoma in WHO and CBTRUS reports. There are statistically significant differences in cystic presentation between glioblastoma group and group of other diffuse gliomas (t=2,4). Cysts are more common in glioblastoma group (44,13%) in comparison with other diffuse gliomas (34,9%). The incidence rate for diffuse gliomas is highest among the 30-54 years age group (48%) and lowest among the 75+ years olds (1,7%). The cystic features are more common among the 0-29 years age group (58,9%). The t-value is 3,4. Except multilobar brain lesions diffuse gliomas are most commonly initially located in the frontal (26%) and temporal lobe (21,7%). Conclusion. 1. The cystic features are more common among the 0-29 years age group. 2. Glioblastoma is the most common tumor among diffuse gliomas. It accounts 54,8% of diffuse gliomas and 25% of primary CNS tumors. 3. Cyst are more common in glioblastoma group in comparison with other diffuse gliomas.